The Impact of Special Autonomy Funds on The Development of Cot Yang Village: Analysis of The Relationship Between Central and Regional Financial - Putra Kaslin Hutabarat; Diva Ramadhani; Amilia Afriana; Samsuar Samsuar; Darlinawati Darlinawati (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: This study examines the impact of Special Autonomy Funds (Otsus) on development in Cot Yang Village, Aceh Besar Regency, focusing on the financial relationship between the central and regional governments and the role of community participation in monitoring fund utilization. This research employs a qualitative method with a case study approach. Data were collected through in- depth interviews with hamlet heads and village officials, field observations, and documentation related to the management of the Special Autonomy Fund. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the main obstacles in the utilization of the Special Autonomy Fund are the lack of transparency and accountability in fund management, as well as the low level of community involvement in the planning and monitoring of development. Limited community participation has led to ineffective development and suboptimal benefits for village residents. This study concludes that improving transparency, accountability, and strengthening community participation are crucial to achieving sustainable development and enhancing community welfare at the village level. Recommendations are directed to the village government to improve fund governance and actively involve residents in every stage of development.Keywords: Special Autonomy Fund, Village Development, Participation, TransparencyAbstrak: Penelitian ini mengkaji dampak Dana Otonomi Khusus (Otsus) terhadap pembangunan di Desa Cot Yang, Kabupaten Aceh Besar, dengan fokus pada hubungan keuangan antara pemerintah pusat dan daerah serta peran partisipasi masyarakat dalam pengawasan penggunaan dana. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui wawancara mendalam dengan kepala dusun dan perangkat desa, observasi lapangan, serta dokumentasi terkait pengelolaan Dana Otonomi Khusus. Teknik analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kendala utama dalam pemanfaatan Dana Otonomi Khusus adalah kurangnya transparansi dan akuntabilitas dalam pengelolaan dana serta rendahnya keterlibatan masyarakat dalam proses perencanaan dan pengawasan pembangunan. Partisipasi masyarakat yang masih terbatas berdampak pada ketidakefektifan pembangunan dan kurang optimalnya manfaat yang dirasakan oleh warga desa. Penelitian ini menyimpulkan bahwa peningkatan transparansi, akuntabilitas, serta penguatan partisipasi masyarakat sangat penting untuk mewujudkan pembangunan yang berkelanjutan dan meningkatkan kesejahteraan masyarakat di tingkat desa. Rekomendasi diberikan kepada pemerintah desa untuk memperbaiki tata kelola Dana Otonomi Khusus dan melibatkan warga secara aktif dalam setiap tahap pembangunan.Kata Kunci: Dana Otonomi Khusus, Pembangunan Desa, Partisipasi Masyarakat, Transparansi